The case against joining the Common Market - Einzig, Paul (London ; Macmillan , [New York] : St. Martin's Press, 1971)
This book is an eleventh hour appeal to the British people and their leaders to think again before committing Britain whether it would be really worth their while to make the sacrifices and take the grave risk involved, for the sake of the dubious results they hope to gain from joining the Common Market.
osc 07/11/2018
Loans
Keywords: Common Markets